Dispersal of Arbuscular Mycorrhizal Fungi: Evidence and Insights for Ecological Studies - Paz, Claudia [UNESP]; Opik, Maarja; Bulascoschi, Leticia [UNESP]; Bueno, C. Guillermo; Galetti, Mauro [UNESP] (Springer, 2020)
Dispersal is a critical ecological process that modulates gene flow and contributes to the maintenance of genetic and taxonomic diversity within ecosystems. Despite an increasing global understanding of the arbuscular mycorrhizal (AM) fungal diversity, distribution and prevalence in different biomes, we have largely ignored the main dispersal mechanisms of these organisms. To provide a geographical and scientific overview of the available data, we systematically searched for the direct evidence on the AM fungal dispersal agents (abiotic and biotic) and different propagule types (i.e. spores, extraradical hyphae or colonized root fragments). We show that the available data (37 articles) on AM fungal dispersal originates mostly from North America, from temperate ecosystems, from biotic dispersal agents (small mammals) and AM fungal spores as propagule type. Much lesser evidence exists from South American, Asian and African tropical systems and other dispersers such as large-bodied birds and mammals and non-spore propagule types. We did not find strong evidence that spore size varies across dispersal agents, but wind and large animals seem to be more efficient dispersers. However, the data is still too scarce to draw firm conclusions from this finding. We further discuss and propose critical research questions and potential approaches to advance the understanding of the ecology of AM fungi dispersal.
Keywords: Glomeromycotina; Propagule; Biotic dispersal; Abiotic dispersal; Mycophagy